The effect of dietary bacterial organic selenium on growth performance, antioxidant capacity, and Selenoproteins gene expression in broiler chickens - A. M., Dalia; Loh, Teck Chwen; Sazili, Awis Qurni; M. F., Jahromi; Samsudin, Anjas Asmara @ Ab Hadi (BioMed Central, 2018)
Background: Selenium (Se) is an essential trace mineral in broilers, which has several important roles in biological processes. Organic forms of Se are more efficient than inorganic forms and can be produced biologically via Se microbial reduction. Hence, the possibility of using Se-enriched bacteria as feed supplement may provide an interesting source of organic Se, and benefit broiler antioxidant system and other biological processes. The objective of this study was to examine the impacts of inorganic Se and different bacterial organic Se sources on the performance, serum and tissues Se status, antioxidant capacity, and liver mRNA expression of selenoproteins in broilers. Results: Results indicated that different Se sources did not significantly (P ≤ 0.05) affect broiler growth performance. However, bacterial organic Se of T5 (basal diet +0.3 mg /kg feed ADS18 Se), T4 (basal diet +0.3 mg /kg feed ADS2 Se), and T3 (basal diet +0.3 mg /kg feed ADS1 Se) exhibited significantly (P ≤ 0.05) highest Se concentration in serum, liver, and kidney respectively. Dietary inorganic Se and bacterial organic Se were observed to significantly affect broiler serum ALT, AST, LDH activities and serum creatinine level. ADS18 supplemented Se of (Stenotrophomonas maltophilia) bacterial strain showed the highest GSH-Px activity with the lowest MDA content in serum, and the highest GSH-Px and catalase activity in the kidney, while bacterial Se of ADS2 (Klebsiella pneumoniae) resulted in a higher level of GSH-Px1 and catalase in liver. Moreover, our study showed that in comparison with sodium selenite, only ADS18 bacterial Se showed a significantly higher mRNA level in GSH-Px1, GSH-Px4, DIO1, and TXNDR1, while both ADS18 and ADS2 showed high level of mRNA of DIO2 compared to sodium selenite. Conclusions: The supplementation of bacterial organic Se in broiler chicken, improved tissue Se deposition, antioxidant status, and selenoproteins gene expression, and can be considered as an effective alternative source of Se in broiler chickens.